Designed folding pathway of modular coiled-coil-based proteins - Jana Aupič (Nature Portfolio, 2021)
Coiled-coil protein origami (CCPO) is a strategy for the design of polyhedral cage-shaped protein folds based on coiled-coil (CC) dimer-forming peptides. Here, the authors show that CCPO proteins fold in a multistep process governed by the spatial distance between CC modules in the primary sequence and subsequent folding intermediates, which enables the use of identical CC modules for the CCPO tetrahedron design.